Urinary schistosomiasis among vulnerable children in a rehabilitation home in Ibadan, Oyo state, Nigeria (2017)
Background: Schistosomiasis is a disease of public health importance with long term complications mostly common among children, rural dwellers, poor and migrant workers. Studies have not documented the burden among migrant workers and their families. The study aimed to describe the burden of schistosomiasis and demographic characteristics among children of migrant workers residing in a rehabilitation home in Ibadan, Nigeria. Methods: A cross-sectional study using sixty six children, who were tested following complaints of haematuria by six of them. An interviewer-administered questionnaire was used to collect information on demographic and environmental characteristics of the children and urine microscopy, was conducted. Data was analysed using descriptive statistics and correlation. Statistical significance was set at 5%. Results: Mean age of respondents was 11.8 ± 4.0 years and 57.6% were males. The prevalence of schistosomiasis was 19.7% with preponderance among males (64.3%) and children aged 12 years and above (71.4%); 85.7% of infected children were from Kwara State; 78.6% waded in water body and 92.9% had red blood cells and pus cells on urine microscopy. Conclusions: The burden of schistosomiasis is high among children of migrant workers and they serve as reservoirs for transmission of the disease. Government needs to work synergistically with NGOs, FBOs and other partners to achieve schistosomiasis prevention and control among this particular group.